Black Coloured Urine following Organophosphorus Poisoning: Report of Two Cases - Aneesh Basheer; Sudhagar Mookkappan; Vijay Shanmugham; Nagarajan Natarajan; Kiran Kulirankal (Case Reports in Critical Care)
Organophosphorus poisoning is common in rural Asia. Clinical features result from overactivity of acetylcholine receptors. Blackish discoloration of urine is not a feature of organophosphorus poisoning. Only one case of black colored urine following quinalphos poisoning has been reported in literature. We report two cases of organophosphorus poisoning from two different compounds, following which patients passed black colored urine, in the absence of haemolysis or rhabdomyolysis. These cases indicate that blackish discoloration of urine in organophosphorus poisoning might not be as uncommon as it was believed to be. Besides, urinary excretion of metabolites might be an underlying mechanism, rather than hemolysis.